Flowering regulation in the facultative biennial Oenothera biennis: environmental effects and their relation to growth rate - Giménez, Raúl (2013)
The lifecycle of the facultative biennial oilseed-crop evening primrose (Oenothera biennis) is a major constraint for its commercial production under different growing conditions, as a variable proportion of plants fails to flower during the first season and remains as vegetative rosettes (biennial behavior). The aim of this work was to understand how flowering is regulated in this species and to identify the main determinants of its biennial behavior. Different planting dates and manipulative treatments (seed vernalization, photoperiod extension and fertilization) were employed to analyze if: (i) biennial behavior occurs when obligate requirements for vernalization or photoperiod are not satisfied; and (ii) responses to these environmental cues depend on the size and/or growth rate of rosettes. Our results indicate that O. biennis has an obligate long-day requirement for flowering and a facultative vernalization response. There is no minimum size requirement for vernalization response (as very small seedlings responded to the vernalization treatment) and the rate of development toward flowering under inductive photoperiods was strongly affected by rosette's growth rate. The incidence of high temperatures just before the onset of reproduction is proposed as an inhibitory factor that prevents reproduction under otherwise photo-inductive conditions. This last factor would explain the high incidence of biennial behavior frequently observed in spring/summer sowing in this crop.